Exploring risk perceptions between pioneer and me-too brands of mp3 players - Quintal, Vanessa; Sims, Daniel (School of Marketing, Curtin Business School, 2009)
The current study examines perceived quality for its differential impacts on the dimensions of perceived risk between the pioneer and me-too brands of MP3 players. To achieve this, a pen and paper survey was administered to students at three Australian universities, since young adults are considered to be lead users of MP3 players. Existing scales were selected for their tested reliability in buying situations and adapted to suit the context of the current study. The constructs demonstrated reliability and convergent and discriminant validity. The perceived equivalent quality of the MP3 players produced significant positive effects on perceived social/physical, financial/performance, time and psychological risks for the pioneer brand and a significant negative effect on perceived financial/performance risk for the me-too brands.